2023
DOI: 10.4274/jcrpe.galenos.2023.2022-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Can Serum 25-Hydroxy Vitamin D Levels Predict the Severity of Multisystem Inflammatory Syndrome in Children and COVID-19?

Abstract: Objective: To determine the clinical significance of serum 25-hydroxy (OH) vitamin D levels in pediatric patients with multisystem inflammatory syndrome in children (MIS-C) and compare the vitamin D levels of these patients with those patients with Coronavirus disease-2019 (COVID-19) and healthy controls. Methods: This study was designed for pediatric patients aged 1 month to 18 years and conducted between July 14 and December 25, 2021. Fifty-one patients with MIS-C, 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Additionally, they found VD insufficiency in 74% of their MIS-C patients, though they used a lower cutoff point for the diagnosis of VD insufficiency (50 nmol/L) than in our research. They also reported that MIS-C patients had significantly lower VD levels than participants in the control group [ 33 ]. A similar high incidence of hypovitaminosis D in pediatric MIS-C patients with a predominance of VD deficiency was found in other studies of different geographical origin [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they found VD insufficiency in 74% of their MIS-C patients, though they used a lower cutoff point for the diagnosis of VD insufficiency (50 nmol/L) than in our research. They also reported that MIS-C patients had significantly lower VD levels than participants in the control group [ 33 ]. A similar high incidence of hypovitaminosis D in pediatric MIS-C patients with a predominance of VD deficiency was found in other studies of different geographical origin [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the number of ≥4 affected organ systems was significantly higher in the group with inadequate 25(OH)D levels. Additionally, they pointed out that patients treated in the PICU had significantly lower 25(OH)D levels than patients in the non-PICU group, and that all of the patients with hypotension and signs of shock had inadequate 25(OH)D levels [ 33 ]. There is a connection between Kawasaki disease, a disease with very similar pathophysiology to MIS-C, and VD mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its non-genomic anti-viral effects [107,108], the genomic actions of calcitriol enhance the transcription of several anti-microbial peptides, such as cathelicidin and defensin [109][110][111]. Vitamin D also stimulates immune cell chemotaxis [112,113] and reduces the severity of COVID-19 [114]. Nevertheless, individual response variations occur due to epigenetic variances [21,80].…”
Section: Figure 4 Causes and Impacts Of Vitamin D Deficiency On Metab...mentioning
confidence: 99%
“…Several studies classified patients according to their serum 25(OH)D level of sufficiency, and variations were noted between the values defined as sufficient, insufficient, and deficient. Studies included in our systematic review determine vitamin D deficiency as levels of serum 25(OH)D less than 20 ng/mL (<50 nmol/L) [16][17][18], less than 12 ng/mL (<30 nmol/L) [9], or between 5 and 15 ng/mL [19], mild deficiency as of 21-30 ng/mL [20], and mild to moderate deficiency as of 10-24 ng/mL [21]. Two studies defined severe vitamin D deficiency as 25(OH)D levels below 10 ng/ml [21,22], and one study as less than 5 ng/mL [19].…”
Section: Findings Of the Included Studiesmentioning
confidence: 99%
“…Those with 25(OH)D levels of 21-29 ng/mL (52.5 and 72.5 nmol/l) [16,17] or 12-20 ng/mL (30-50 nmol/L) [9,23] were defined as vitamin D insufficient, and those with levels above 30 ng/ml (75 nmol/L) were considered to have normal levels [16,17]. COVID-19 disease was classified as asymptomatic, mild, moderate, severe, and critical according to clinical presentation.…”
Section: Findings Of the Included Studiesmentioning
confidence: 99%